Відображення протистояння Янку Флондора та Іона Ністора на сторінках газети «Bucovina» у 1919 р. - Піддубний, Ігор (Чернівці-Сучава: БДМУ., 2021)
The incorporation of Bukovina into the Kingdom of Romania set the political leaders of the Romanians of Bukovina the task not only of rebuilding the region after World War, but also of finding consensus in their actions aimed at creating a new country. The desire to preserve the special features and inherent institutions of the region from the Austrian era gave rise to confrontation between Yanku Flondor and Ion Nistor which was reflected in the publications of the Bukovina press. The aim. The aim of the article is to introduce into scientific circulation information on the confrontation between two Romanian political groups in Bukovina and its coverage in the Bukovina press. Research methods. In the publication used a synchronous approach and special historical methods. In particular, we used to study the situation comparative, problem-chronological methods, synchronous. the latter allows us to trace the sequence in the context of political changes in Bukovina, the evolution of the opposition's views, its search for ways to influence the population of the region. the application of the synchronous method makes it possible to establish and monitor the reaction of the opposition and pro-government to the actions of the opposite party. The scientific novelty. The scientific novelty of this article is to cover for the first time in Ukrainian historiography the confrontation between two representatives of the Romanian political camp in Bukovina and its reflection in the publication of the opposition group of Yanku Flondor to the government group. Conclusions. In general, the use of the Bucovina newspaper in the political life of the region should be considered a manifestation of the activities of a group of politicians who considered it their task to preserve the status quo of Bukovina as part of the Kingdom of Romania. In their activities, they used the norms and techniques known since the development of the national movement in the late nineteenth – early twentieth century. However, the forms of protest did not achieve the desired result in the new conditions, removing the opposition from the opportunity to act also by parliamentary methods.
Отражение противостояния Янку Флондора и Иона Нистора на страницах газеты “Bucovina” в 1919 г.
Reflection of the confrontation between Yanku Flondor and Ion Nistor on the pages of the newspaper “Bucovina” in 1919
Keywords: Iancu Flondor; Ion J. Nistor; Bukovina; Bukovina crisis of 1919